SINKRONISASI DATABASE TERHADAP PENGIRIMAN DATA SMS MENGGUNAKAN MULTIPLE MODEM SMSGATEWAY - Affandi, Luqman; Suryani, Dhebys; Prima A, Putra (DINAMIKA DOTCOM, 2018)
SMS Gateway Server will connect with a database whichÂ  will be sent via sms sender modem. When a message is sent to the recipient, the time required to send the SMS is for a long time. To be able to solve these problems can be used multiple modem, so the sms delivery expense can be divided into several modems in one delivery. This requires the technique of how to manage the sms recipients in order to be well distributed to multiple modems at once. The technique that can be used is database synchronization with multiple modems, by dividing the number of messages to be sent. Such data synchronization can save about 50% of the time of delivery.Â Keyewords: SMS Gateway, synchronization, time of delivery